Hubungan Paparan Timbal Dalam Darah dengan Kejadian Hipertensi Pada Pekerja Industri Pengecoran Logam Di Ceper Klaten Tahun 2015 - Ambarwanto, Sigit Tri; Nurjazuli, Nurjazuli; Raharjo, Mursid (Jurnal Kesehatan Lingkungan Indonesia, 2015)
Background: The problem of heavy metal pollution is a serious problem in Indonesia. This metal has been known to be stored in the body for long periods of time as toxins accumulate. Preliminary test results BLL on workers in the metal casting Ceper, found as many as 16 (5.61%) BLL on workers is under (NAB) and 17 (5.28%) workers above (NAB). The research was conducted to determine the relationship between the exposure of lead (Pb) in blood with hypertension in foundry workers CV. Fortification Jaya Batur, Ceper, Klaten. Methods: It was an observational study with Cross Secional design. The population in this study were all workers CV. Jaya fortification. Samples are workers CV. Fortification Jaya who met the inclusion criteria. Gathering data using questionnaires tools, inspection PB in the air using Gravimetry, Pb in the blood examination using AAS (automatic Absorption Spectrophotometer) and hypertension examination tension meter is measured using a needle. Results: The average air Pb 0.13756 mg / dl, the average BLL was 14.38096Î¼g/dl. Chi Square test results showed that there was no relationship between the type of work with hypertension (p = 0.625), There is a relationship between levels of air Pb Pb levels in blood (p = 0.019), There is a relationship between levelsof lead in blood with hypertension(p=0.042).Conclusions:Levels of Air Pb Pb levels in the blood affects that can cause hypertension.Â Keywords: Hypertension, Blood Lead Level, Klaten